The efficacy and safety of an indocyanine green−hyaluronic acid mixture (LuminoMark™) for localization in patients with non-palpable breast lesions: A multicenter, randomized, open-label, parallel phase 3 clinical trial - Bang, Yoon Ju; Choi, Hee Jun; Kim, Isaac; Lee, Moo-Hyun; Lee, Seeyoun; Shin, Hyuk Jai; Nam, Seok Jin; Lee, Jeong Eon; Chae, Byung-Joo; Lee, Se Kyung; Ryu, Jai Min; Kim, Seok Won (Frontiers in Oncology, 2023)
Purpose The incidence of early tumor detection is increasing due to popularization of breast cancer screening and the development of imaging techniques. Thus, suitable preoperative localization is required for proper diagnosis and treatment of non-palpable breast lesions. The purpose of this study was to evaluate the efficacy and safety of indocyanine green (ICG)-hyaluronic acid (HA) mixture for lesion localization compared to activated charcoal. Methods This was a multicenter, randomized, open-label, parallel phase 3 clinical trial performed at four centers in Korea. Female patients scheduled for surgery to remove non-palpable breast lesions were enrolled. One hundred and nine patients were randomly assigned to a control group (activated charcoal: 0.3. – 1 mL) or a study group (ICG-HA mixture, 0.2 mL) for the localization of a breast lesion. The primary endpoint was the accuracy of resection. Secondary endpoints included the technical success rate, histopathological accuracy, skin pigmentation rate, and adverse event rate. Results A total of 104 patients were eligible for per-protocol analysis (control group, n = 51; study group, n = 53). The accuracy of resection in the study group was not inferior to that of the control group (90.57% vs. 98.04%, 95% confidence interval (CI): -2.31 – 18.91, p = 0.21). There was no statistically significant difference in technical success rate between the two groups (marking on breast skin: p = 0.11, marking on the excised specimen: p = 0.12). However, there were statistically significant differences in histopathological accuracy (0.26 ± 0.13 vs. 0.33 ± 0.17, p = 0.01) and skin pigmentation rate (0.00% vs. 30.77%, p< 0.01). Adverse events were not reported in either group. Conclusions When localization was performed using ICG-HA, the accuracy of resection was not inferior to that of activated charcoal. However, skin pigmentation rate was significantly lower. In conclusion, ICG-HA is effective and safe for localizing of non-palpable breast lesions.